Food Waste Management 2019
DOI: 10.1007/978-3-030-20561-4_10
|View full text |Cite
|
Sign up to set email alerts
|

From Scarcity to Abundance: Food Waste Themes and Virtues in Agrarian and Mature Consumer Society

Abstract: Uusitalo and Takala address food waste problem as a societal phenomenon and examine ethical virtues, values linked to them, and food practices in two different time periods, agrarian society and mature consumer society (2008)(2009)(2010)(2011)(2012)(2013)(2014)(2015)(2016)(2017), in Finland. Their study uses data from newspapers to uncover how ethical principles can underpin understanding of food waste phenomenon. The study shows how the virtues adopted by food chain actors guide their practices towards susta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
0
2
0
2
Order By: Relevance
“…The discursive basis of the appreciation framing intertwines cultural values and the frugal Finnish heritage of not wasting (Huttunen and Autio 2010;Uusitalo and Takala 2020). This framing stems from the idea that people no longer appreciate food and, as a consequence, create food waste.…”
Section: Appreciation Framingmentioning
confidence: 99%
“…The discursive basis of the appreciation framing intertwines cultural values and the frugal Finnish heritage of not wasting (Huttunen and Autio 2010;Uusitalo and Takala 2020). This framing stems from the idea that people no longer appreciate food and, as a consequence, create food waste.…”
Section: Appreciation Framingmentioning
confidence: 99%
“…Ruoan tuhlaaminen on yhdistetty resurssien haaskaamiseen (esim. Evans ym., 2013;Uusitalo & Takala, 2020), jo kauan ennen kuin sitä on alettu käsitellä moniulotteisena ilmiönä, jona se tänä päivänä tunnistetaan (Pollari, 2022, 136). Olemmekin siirtyneet niukkuuden yhteiskunnasta runsauden yhteiskuntaan vain muutaman sukupolven sisällä, mikä saattaa näkyä sukupolvien välisinä näkemyseroina ruokaan liittyvissä käytännöissä ja arvostuksissa.…”
Section: Ruokakasvatus Ja Ruokahävikkiunclassified
“…Tulostemme taustalla on kulttuurinen muutos, jossa tutkitut yhteiskunnat ovat siirtyneet niukkuudesta ja säästäväisyydestä vaurauteen ja runsauteen ja pidättäytyvyydestä nautinnon ja terveyden väliseen tasapainotteluun (Uusitalo & Takala, 2020;Salonen, 2021Salonen, , 2018. On ehdotettu, että tällainen yhteiskunta on hylännyt kohtuullisuuden ihanteen (Raunio, 2014).…”
Section: Johtopäätökset Ja Pohdintaunclassified
“…Thrift and frugality are deep-rooted cultural ideals originating from the Protestant Reformation in the 1500s. They have dominated Finnish cultural ideologies of consumption and principles of good citizenship particularly since the rise of bourgeois household ideologies and household advice given by elites to the people from the end of the 1800s onwards (Aro 2010;Heinonen 1998;Åström 2010;Uusitalo & Takala 2020). It has been shown that those generations born soon after the Second World War still produce less food waste (Parfitt, Barthel & Macnaughton 2010: 3079) and value thrift and frugality rather than endorse environmental values (Aro 2010;Evans 2011;Hebrok & Boks 2017: 383).…”
Section: Thrift and Frugalitymentioning
confidence: 99%